2012
DOI: 10.1002/dneu.20989
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of a portion of the native SNCA 3′UTR reduces toxicity of human S129A SNCA on striatal‐projecting dopamine neurons in rat substantia Nigra

Abstract: Experimental models of Parkinson’s disease (PD) created by aberrant expression of the alpha-synuclein (SNCA) coding region have been reported. However, non-coding regions function in normal physiology and recent in vitro studies have shown that microRNAs-7 and -153 regulate SNCA expression by binding the 3′UTR. Here, effects of different hSNCA forms were examined in vivo. Adult, male rats were injected into one substantia nigra (SN) with AAV-wtSNCA, AAV-S129A hSNCA, or AAV-S129DhSNCA either with or without a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…These results are in accordance with the report that the regulation of human alpha-synuclein at its 3 0 UTR also decreases its levels and toxicity in vivo. 54 Interestingly, overexpression of mutATXN3-3 0 UTR in vivo resulted in remarkably low toxicity. Notably, this finding is in accordance with the previously mentioned MJD transgenic mouse models that include the 3 0 UTR of ATXN3.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in accordance with the report that the regulation of human alpha-synuclein at its 3 0 UTR also decreases its levels and toxicity in vivo. 54 Interestingly, overexpression of mutATXN3-3 0 UTR in vivo resulted in remarkably low toxicity. Notably, this finding is in accordance with the previously mentioned MJD transgenic mouse models that include the 3 0 UTR of ATXN3.…”
Section: Discussionmentioning
confidence: 99%
“…This phosphorylation is also found in pre‐LB stages suggesting that it is strongly associated to disease progression (Saito et al., ). The pharmacological modulation of this phosphorylation may be a relevant strategy for slowing PD progression, although several studies show α‐syn‐related toxicity is enhanced when the Ser129 residue is mutated to an unphosphorylatable alanine residue (Da Silveira et al., ; Gorbatyuk et al., ; Khodr, Pedapati, Han, & Bohn, ). Some kinase interactors have been identified that can modulate Ser129 phosphorylation including polo‐like kinases, casein kinases, and G protein‐coupled receptor kinase (Inglis et al., ; Ishii et al., ; Pronin, Morris, Surguchov, & Benovic, ).…”
Section: α‐Syn and Prion‐like Propagationmentioning
confidence: 99%
“…This type of regulation plays an essential role in the transition of normal to pathogenic functions of α-synuclein [24][28]. At least two miRs, miR-7 and miR-153 are involved in 3′-UTR mediated negative control of α-synuclein expression [27][30]. Furthermore, miR-133b is deficient in the Parkinson’s disease midbrain, and miR-34b/34c is decreased in certain brain regions in patients [24].…”
Section: Introductionmentioning
confidence: 99%